The role of artificial intelligence in innovative management: international experience and Kazakhstan’s opportunities (Journal of Economic Research & Business Administration, 2025)
It is widely recognized that the potential of artificial intelligence (AI) is incredibly multifaceted. With its help, tasks and services that could previously only be performed by humans are now performed quickly and efficiently using various available technologies. AI makes life much easier by effectively solving technical problems and optimizing many processes. As a key driver of the fourth industrial revolution, artificial intelligence has a profound impact on the productivity of organizations, fundamentally changing existing business models and stimulating innovation processes.Since the term “artificial intelligence” appeared in the scientific field, research aimed at its development has been actively conducted. However, AI is still a relatively new and complex technology that has not been fully studied.As for the impact of artificial intelligence on innovation management, AI has the potential to radically change practices in this area. These changes will open a new era in innovation management, making innovation processes more efficient and successful. However, our knowledge of the use of AI in innovation management is still limited, and managers continue to search for the most effective ways to apply this technology.This article examines the role of artificial intelligence in innovation management by analysing the theoretical aspects of innovation management and AI, identifying their interrelationship, and assessing the potential for effectively applying AI in managing innovative activities in Kazakhstani organisations. Using an evolutionary approach, the article evaluates international experience, while the induction method is applied to forecast the potential use in Kazakhstan’s innovation management sector.The novelty of this study lies in the first-ever examination of AI’s application, role, and conceptual foundation within innovative activities in Kazakhstani organisations. The legal framework for informatisation and AI development in Kazakhstan has been established. However, AI development requires substantial financial support and stronger collaboration between science, industry, and enterprises.Key words: innovation, innovation management, artificial intelligence, sustainable development, economy, strategy.